KUALITAS HIDUP PENDERITA HIPERTENSI DI PUSKESMAS PUNDONG KECAMATAN PUNDONG, KABUPATEN BANTUL, YOGYAKARTA - Ekatrina WIjayanti; Theresia Titin Marlina (STIKES Wira Husada Yogyakarta, 2018)
ABSTRACTBackground: Hypertension is called the silent killer because it often has no warning sign and sympthom and many people do not know they have it. Hypertension are increasing and 54% have uncontrolled blood pressure even 63,2% are undiagnosed. Based on interviews with patients in the Pundong Health Center, data was obtained that they did not realize that their blood pressure was high if there were no complaints. Even hypertension has been diagnosed, they are not routine control and there is no attempt to control blood pressure. Objective: to determine the quality of life of patients with hypertension at Pundong Health Center. Methods: quantitative research with a cross-sectional study. Samples were taken randomly, total of 70 people. Instrument uses WHOQoL-BREF. Analysis of data with percentages. Results: The quality of life of patients with hypertension in physical health domains was moderate 78.6%, good 18.6% and bad 2.9%. The domain of psychological well-being was moderate 81.4%, bad 15.7% and good 2.9%. The social relations domain was good 47.1% and moderate 45.7%, very bad 5.7% and bad 1.4%. The environmental domain was 70% moderate, 25.7% good and 4.3% bad.Conclusion: The quality of life of patients with hypertension are moderate quality of life, but there are still some sufferers who have a bad quality of life of 2.9-15.7% in the domain of physical health, psychological well-being, social and environmental relations.